Tinjauan Komplementer Pengaruh Teori Market-Based View (MBV) dan Resource-Based View (RBV) terhadap Strategi dan Kinerja Perusahaan - Simatupang, Boto (Binus Business Review, 2013)
The influence of the strategy to company performance is the most widely researched topic until now. Various literatures state that the influence of company performance to strategy does not stand alone, but is affected by a variety of external and internal contingency factors. The discussion in this paper begins with a description of the two major strategic management theories in the theory of MBV and RBV. So both theory of RBV and MBV theory indeed complement each other and have an important role in explaining the influence of strategy to the company performance. This research aims to prove which theory is much more instrumental in explaining the influence of strategy on performance is not important to do, because this is futile efforts .